KAJIAN STRUKTUR SOSIAL MASYARAKAT NELAYAN DI EKOSISTEM PESISIR (Study of Social Structure of the Fisherman Community in Coastal Ecosystem) - Emi Handrina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Research aim is to analyse any social changes and dynamic of space capacity and critical point of social structure in coastal ecosystem. The main factor of structural change is external factor of structural formation (individu , system), or increase of community access to the change of local social environment, and external social environment. Dynamics of space capacity of social structure in coastal ecosystem of Bungus Teluk Kabung Padang during periode of research can be explained through the two indicators, objective and subjective. There are a general critical point and a special critical point. This results explain that a evolution theory suggest a high possibility to be synthesized with any other theories, e.g. a conflict theory, an equilibrium theory, and a “timbul-tenggelam” theory. The synthesis process is an operational stage in a schematic mapping of theories by Appelbaum. Dynamics of social structure must be known bt any goverment and NGO, which have any development plans in the fisherman community.